Transforming Higher Education in Mongolia - Badarch, Dendev; Munkhbold, Badarch (International Higher Education, 2025)
This paper provides an overview of the Mongolian higher education sector and presents the challenges that it faces. It then delves into some of the opportunities that would allow the sector to overcome the challenges that it faces, provided that they are properly managed.